Neoadjuvant T-DM1/pertuzumab and paclitaxel/trastuzumab/pertuzumab for HER2+ breast cancer in the adaptively randomized I-SPY2 trial - Amy S. Clark (Nature Portfolio, 2021)
HER2-targeted therapy improves patient’s outcome in early breast cancer. Here, the authors present the efficacy and biomarker analysis of two HER2-targeted combinations (ado-trastuzumab emtansine plus pertuzumab and paclitaxel, trastuzumab and pertuzumab) in the context of the neoadjuvant I-SPY2 phase 2 adaptive platform trial for early breast cancer at high risk of recurrence.